Lobomycosis in Amazon Region, Bolivia, 2022 (2024)
We report a patient with lobomycosis caused by Paracoccidioides loboi fungi in the Andes-Amazon region of Bolivia. We examined clinical, epidemiologic, and phylogenetic data and describe potential transmission/environmental aspects of infection. Continued surveillance and identification of lobomycosis cases in South America are crucial to prevent the spread of this disease.